2020
DOI: 10.1108/jec-09-2019-0088
|View full text |Cite
|
Sign up to set email alerts
|

Selling culture: a buy local campaigns in the Ghanaian and South African textile and clothing industries

Abstract: Purpose This paper aims to examine the paradoxes of buy local campaigns. These are popular strategies for marketing products in domestic markets aimed at supporting the local economy. Their scope can be national, regional, community or sectoral (such as agriculture, tourism, clothing or textiles). Design/methodology/approach This paper examines the paradoxes associated with these campaigns, using two cases and a mixed methods study of buy local campaigns in the Ghanaian and South African textiles and clothin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…However, running a business can increase women's status in society and reduce dependence on others. Our results showed that WHBBs can an important role in the family [24] and society, if supported financially, given proper training, and access to markets [71]. Although their businesses differ from one another in terms of investment, income earned, training, and education, each WHBB contributes to the family's financial wellbeing and managing the challenges of work-life interactions in the extended family system.…”
Section: Discussionmentioning
confidence: 73%
“…However, running a business can increase women's status in society and reduce dependence on others. Our results showed that WHBBs can an important role in the family [24] and society, if supported financially, given proper training, and access to markets [71]. Although their businesses differ from one another in terms of investment, income earned, training, and education, each WHBB contributes to the family's financial wellbeing and managing the challenges of work-life interactions in the extended family system.…”
Section: Discussionmentioning
confidence: 73%
“…Currently, in most developing countries, including Pakistan, industrialized products have captured markets, which makes it difficult for traditional handicraft communities to make a living (Forero-Montaña et al, 2018;Yang et al, 2018). As the community enterprises offer potential sustainable development strategies for the disadvantaged rural poor peoples (Anwar et al, 2019;Darku and Akpan, 2020;Dissanayake et al, 2017;Ferreira et al, 2019;Gao and Wu, 2017;Wanniarachchi et al, 2020), most rural communities usually depend on the income earned through handicraft production. Hence, there is a need to revive this industry; else, the cultural heritage embodied in crafts may fade away soon.…”
Section: Introductionmentioning
confidence: 99%
“…Disregarding the significant relationship between GMS and consumer purchase intention identified, ALP is not relevant to the decision in determining this relationship. Related to that, Darku & Akpan (2020) revealed that the efficacy level of buying the local product is highly dependent on the level of ethnocentrism and the nature of the market. It might imply that respondents did not have extreme ethnocentrism toward local products.…”
Section: The Moderation Resultsmentioning
confidence: 98%
“…Nevertheless, they did not mention how Muslim consumers were interested in green products. Meanwhile, the government's campaign to buy local products has generated consumer awareness (Darku & Akpan, 2020). Therefore, as a case study, this research addresses the gap in the current articles regarding the moderating role of consumer attitudes towards local products on GMS and purchase intention with Muslim consumers at Banjarmasin.…”
Section: Introduction 11 Backgroundmentioning
confidence: 99%